INTERNALISASI NILAI ADAB SISWA MENURUT AL-GHAZALI DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK - Zulfa Istinwaro Holik; Yuliana; Bunga Dewi; Benny Prasetiya (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2026)
This study aims to examine the concept of internalizing moral values (adab) according to Al-Ghazali and to identify its implications for the character formation of students in the contemporary era. Background: of this research stems from the importance of adab as a foundational element of education according to Imam Al-Ghazali. In light of the rampant moral degradation observed in students during the modern era, Al-Ghazali's ideas are deemed relevant in reinforcing educational objectives that emphasize not only intellectual abilities but also character formation, spirituality, and noble personality. Method: This research employs a literature review method with content analysis of Al-Ghazali's primary works such as "Ihya’ Ulumuddin" and "Ayyuha al-Walad," as well as pertinent secondary references. A source triangulation technique is used to ensure the validity of the findings through the comparison of various classical and contemporary literature. Results: The study indicates that the internalization of adab can be achieved through habituation, exemplary behavior, purification of the soul (tazkiyatun nafs), self-control, and fostering a respectful relationship between teachers and students. Key moral values, such as sincerity in learning, discipline, respect for teachers, and strengthening of spirituality, are essential in comprehensively shaping students' characters. Al-Ghazali's thoughts also prove relevant as solutions to moral issues in the digital age and globalization. Conclusion: The research emphasizes that character education based on Al-Ghazali's adab is critical in cultivating students who are morally upright, knowledgeable, and emotionally as well as spiritually mature. The internalization of adab is not only vital within the school context but also requires the roles of families and communities to establish a holistic educational ecosystem.